Preserving Healthcare Privacy : A fusion of Blockchain and Self Soverign Identity - Monica Chawla (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research delves into the intricate landscape of blockchain adoption, particularly its implications for user and data privacy concerns, especially in the context of enterprises accumulating and safeguarding user data. The transparency inherent in public blockchains raises pivotal questions surrounding data ownership and privacy. The study underscores the imperative to identify and accentuate privacy-focused blockchain technologies, proposing a standardized Blockchain Reference Model for development practices. Within the healthcare domain, the integration of self-sovereign identity (SSI) with blockchain technologies emerges as a salient focus. The research elucidates the impact of this integration on privacy-preserving mechanisms, encompassing decentralization, verifiable credentials, user control, data minimization, consent management, immutable audit trails, revocation, and secure key management. This research paper investigates the evolving landscape of blockchain technologies, with a specific focus on their integration with self-sovereign identity (SSI) in healthcare applications.. Within the healthcare sector, the integration of SSI with blockchain technology emerges as a strategic avenue. The research explores the impact of this integration on privacy-preserving mechanisms, encompassing decentralization, verifiable credentials, user control, data minimization, consent management, immutable audit trails, revocation, and secure key management. Addressing privacy and security compliance challenges in healthcare necessitates a multifaceted approach, involving technological advancements, educational initiatives, and rigorous regulatory adherence. The delicate balance between enabling data accessibility for healthcare professionals and implementing robust security measures is underscored as pivotal for successful information system management in healthcare data. The paper concludes with an in-depth examination of the symbiotic relationship between self-sovereign identity and blockchain technology. The openness of public blockchains poses critical considerations about data ownership and privacy. The report emphasizes the need of identifying and emphasizing privacy-focused blockchain technology, and it proposes a standardized Blockchain Reference Model for development procedures. The integration of self-sovereign identification (SSI) with blockchain technology is a prominent emphasis in the healthcare area. The study investigates the effect of this integration on privacy-protection methods such as decentralization, verified credentials, user control, data minimization, consent management, immutable audit trails, revocation, and secure key management. A holistic strategy to addressing privacy and security compliance issues in healthcare is being developed.